How Much Should We Trust Estimates of Firm Effects and Worker Sorting? - Bonhomme, Stéphane; Holzheu, Kerstin; Lamadon, Thibaut; Manresa, Elena; Mogstad, Magne; Setzler, Bradley (Journal of Labor Economics, 2023)
Many studies use matched employer-employee data to estimate a statistical model of earnings determination with worker and firm fixed effects. Estimates based on this model have produced influential yet controversial conclusions. The objective of this paper is to assess the sensitivity of these conclusions to the biases that arise because of limited mobility of workers across firms. We use employer-employee data from the United States and several European countries while taking advantage of both fixed effects and random effects methods for bias correction. We find that limited mobility bias is severe and that bias correction is important.